2009
DOI: 10.1038/ejhg.2009.154
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution SNP arrays in mental retardation diagnostics: how much do we gain?

Abstract: We used Affymetrix 6.0 GeneChip SNP arrays to characterize copy number variations (CNVs) in a cohort of 70 patients previously characterized on lower-density oligonucleotide arrays affected by idiopathic mental retardation and dysmorphic features. The SNP array platform includes B900 000 SNP probes and 900 000 non-SNP oligonucleotide probes at an average distance of 0.7 Kb, which facilitates coverage of the whole genome, including coding and noncoding regions. The high density of probes is critical for detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 44 publications
4
56
0
Order By: Relevance
“…Lately, however, genetic aetiology has been determined for more and more ID / DD cases, especially in developed countries. Within our investigation we have discovered genetic testing to be informative only for a percentage (40.5%) of all ID / DD patients, which is in line with similar studies where genetic predisposition is reported in 17-47% of cases (5,10). According to our results, the genetic diagnosis was most commonly established in infancy and in more severely affected patients, when besides ID / DD, congenital anomalies and dysmorphic features were present.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Lately, however, genetic aetiology has been determined for more and more ID / DD cases, especially in developed countries. Within our investigation we have discovered genetic testing to be informative only for a percentage (40.5%) of all ID / DD patients, which is in line with similar studies where genetic predisposition is reported in 17-47% of cases (5,10). According to our results, the genetic diagnosis was most commonly established in infancy and in more severely affected patients, when besides ID / DD, congenital anomalies and dysmorphic features were present.…”
Section: Discussionsupporting
confidence: 76%
“…However, at present specific aetiology can only be described in about 50% of the cases, while the rest remains elusive (5). Combined data from a number of related studies suggest that about 17-47% of all ID / DD cases could be attributed to genetic abnormalities (6).…”
Section: Introductionmentioning
confidence: 99%
“…The limited contribution of an increment in the number of probes to ϳ 500,000 is also illustrated by the finding of Friedman et al [2009] that among 44 MR/MCA patients who tested negative on a 100,000 SNP genotyping platform, only 1 tested positive when all 44 were reanalyzed using a 500,000 SNP platform. Similarly, Bernardini et al [2009] reanalyzed 51 patients, who scored normal using a 44,290 oligonucleotide array-CGH platform, on a SNP genotyping platform containing 1,800,000 probes, and a pathogenic imbalance was detected in only 3 of these patients. It seems, therefore, that the position of the probes relative to dosagesensitive regions of the genome is more critical than probe number.…”
Section: Idiopathic Mental Retardation With or Without Congenital Abnmentioning
confidence: 99%
“…Causes of mental retardation are numerous and include genetic and environmental factors [4]. Anything that damages and interferes with the growth and maturation of the brain can lead to MR, and this might happen before, during or after the birth of the child [1,3]. Though it is generally assumed that half of the cases are due to genetic factors, the cause of the handicap in up to 50% of patients remains unexplained [5].…”
Section: Introductionmentioning
confidence: 99%
“…MR etiology is very heterogeneous and unfortunately, in about more than half the cases the cause of MR is still elusive [3]. Causes of mental retardation are numerous and include genetic and environmental factors [4].…”
Section: Introductionmentioning
confidence: 99%